Measurement of the Carbon Footprint in the Company Sistemas Operativos Móviles, Transmilenio - Díaz, Carlos; Rodríguez, William; Pinzón, Erik; Vega, Adm Stephanie (TECCIENCIA, 2014)
One of the main environmental problems affecting the current world is related to climate change; high CO2 emissions of greenhouse gases have intervened directly with this change. The purpose of this study was to measure the carbon footprint that supposes the quantification of greenhouse gases by using the basic principles and requisites of the ISO 14.064-1: 2006 standard; specifications aimed at the organizational level to quantify and notify greenhouse gas emissions. The study was conducted in the company Sistemas Operativos Móviles, Transmilenio, which has an active fleet of 160 articulated buses.